2016
DOI: 10.2118/180736-pa
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Multiphase Behavior for n-Butane/Bitumen/Water Mixtures

Abstract: Summary Steam/solvent coinjection has been studied and pilot tested as a potential method to improve steam-assisted gravity drainage (SAGD) for bitumen recovery. Reliable design of coinjection requires reliable pressure/volume/temperature (PVT) data for bitumen/solvent/water mixtures, which are scarce and fragmentary in the literature. The main objective of this research was to present a new set of PVT and multiphase data for n-butane/Athabasca-bitumen/water mixtures at pressures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…As mentioned previously, the entire database has been divided into four groups, that is, the light-saturated hydrocarbons, heavy-saturated hydrocarbons, aromatic compounds, and other compounds. As for the heavy-oil recovery processes, the light-saturated hydrocarbons are related to the light-components in heavy oil and injected solvents, the heavy-saturated hydrocarbons are related to the heavy paraffins in heavy oil, and the aromatic compounds are related to the aromatics, resins, and asphaltenes in heavy oil. To examine the effects of these three categories on the optimum reduced temperature and vapor pressure predictions for which the PR-EOS is used as the example, the variation of AARDs for the light-saturated hydrocarbons, heavy-saturated hydrocarbons, and aromatic compounds with reduced temperature are respectively plotted in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned previously, the entire database has been divided into four groups, that is, the light-saturated hydrocarbons, heavy-saturated hydrocarbons, aromatic compounds, and other compounds. As for the heavy-oil recovery processes, the light-saturated hydrocarbons are related to the light-components in heavy oil and injected solvents, the heavy-saturated hydrocarbons are related to the heavy paraffins in heavy oil, and the aromatic compounds are related to the aromatics, resins, and asphaltenes in heavy oil. To examine the effects of these three categories on the optimum reduced temperature and vapor pressure predictions for which the PR-EOS is used as the example, the variation of AARDs for the light-saturated hydrocarbons, heavy-saturated hydrocarbons, and aromatic compounds with reduced temperature are respectively plotted in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Another important category of heavy oil components is the heavy-saturated hydrocarbons. Since the critical temperatures of heavy-saturated hydrocarbons are relatively high, the temperature range of the data points of the heavy-saturated hydrocarbons is also high . For instance, the average temperature of the data points of the heavy-saturated hydrocarbons in the existing database is 252.20 °C, which is higher than the operating temperature of regular solvent recovery processes for enhancing heavy-oil recovery. By adding vapor pressures of heavy-saturated hydrocarbons at average temperature of 166.80 °C to the newly expanded database, the data points can be more related to the operating temperature range of the relevant solvent recovery processes. Also, it is found that the optimized alpha functions for the entire database, heavy-saturated hydrocarbons, and aromatic compounds, have almost the same optimum reduced temperature for the acentric factor, which is around 0.59 (see Table ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the L phase represents the hydrocarbon-rich liquid phase, which is mainly composed of heavy oil and solvents, while the V phase refers to the vapor phase, which is mainly composed of gaseous solvents. Numerous efforts have been devoted to investigating the multiphase boundaries of the water/solvent(s)/hydrocarbon systems under reservoir conditions in the pressure–temperature space (i.e., P – T phase diagram). However, few attempts have been made to determine the multiphase behavior regarding the aforementioned systems in terms of isenthalpic flash. Specifically, isenthalpic flash should be employed to quantify the phase behavior for the aforementioned steam injections because energy (i.e., enthalpy) is constant and temperature varies within the reservoir. Therefore, it is of fundamental and practical importance to determine the ALV phase boundaries in both the P – T phase diagram and enthalpy–temperature space (i.e., H – T phase diagram) for the water/solvent(s)/hydrocarbon systems for steam-solvent coinjection processes.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al determined the phase behavior including phase boundaries, volumes, and compositions of C 3 H 8 /CO 2 /heavy oil mixtures with the existence of water by applying two different alpha functions for water and nonwater components, respectively. Gao et al experimentally measured multiphase boundaries of n -C 4 H 10 /bitumen/water mixtures at temperatures and pressures as high as 160 °C and 10 MPa, respectively. Chen and Yang developed a new and pragmatic methodology to determine multiphase boundary pressures and their types together with mutual solubilities of solvents/heavy oil/bitumen/water systems within a wide temperature span of 298–573 K for different kinds of heavy oils by using new binary interaction parameters (BIPs) in the Peng–Robinson equation of state (PR EOS).…”
Section: Introductionmentioning
confidence: 99%